Maternal Perceived Stress and Positive Mother-Child Communication in Early Childhood: A Multidimensional Study in Indonesia - Qayyima, Zetamilla; Nurwianti, Fivi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
This study examined the association between maternal perceived stress and positive mother-child communication in early childhood. Although communication is central to children’s socioemotional development, less is known about how maternal stress is related to specific dimensions of communication in non-Western caregiving contexts. Using a quantitative cross-sectional design, this study involved 229 Indonesian mothers of children aged 0 to 8 years. Maternal perceived stress was measured using the Perceived Stress Scale, while mother-child communication quality was assessed using an adapted version of the Parent-Child Communication Quality Scale, which includes four dimensions: empathy, mirroring, idealization, and appropriate response. Data were analyzed using a series of linear regression models. The results showed that maternal perceived stress was significantly and negatively associated with overall mother-child communication quality. Separate regression analyses further indicated significant negative associations between perceived stress and all four communication dimensions. Empathy showed the strongest negative association, followed by mirroring, idealization, and appropriate response. These findings suggest that communication processes requiring stronger emotional attunement and perspective-taking may be more closely linked to maternal stress than more routinized behavioral responses. This study contributes to global parenting and early childhood literature by offering evidence from an Indonesian context and by showing the value of examining mother-child communication as a multidimensional construct. However, the cross-sectional design and reliance on self-report measures limit causal interpretation. Future research should employ longitudinal and multi-method approaches, including observational assessment, to examine how maternal stress, emotion regulation, and contextual family factors shape mother-child communication across diverse cultural settings.